A summary of reports of abyssal and hadal Monoplacophora and Polyplacophora (Mollusca) - Schwabe, Enrico (Zootaxa, 2008)
A summary of literature records of Polyplacophora and Monoplacophora from below 2000 m is presented. Reports have been published of 11 described species of monoplacophorans and twice as many polyplacophorans from abyssal and hadal depths. Additionally taken into account are several records of deep water species of uncertain taxonomic position in both classes. Occurrence and geographic distribution are briefly discussed.